Phát triển năng lực đánh giá kết quả giáo dục học sinh cho sinh viên đại học sư phạm ngành Giáo dục tiểu học - Bùi Đức Nhân, Bùi Đức Nhân; Phan Trung Kiên, Phan Trung Kiên (Tạp chí Giáo dục, 2026)
In response to the requirements of innovating student assessment, primary school teachers must not only thoroughly understand these reforms but also possess the competence to implement them correctly and fully. Accordingly, the issue of developing professional competence in general, and student assessment competence in particular, for undergraduate students majoring in Primary Education needs to be addressed with comprehensive solutions. However, research on developing assessment competence for primary students remains limited, especially regarding the development of this capacity for students in primary education programs. By employing theoretical research methods and building upon findings from various studies on student assessment conducted since 2007, this article provides an in-depth theoretical analysis of developing assessment competence for Primary Education students. This includes: objectives, contents, developmental stages, and factors influencing the development of student assessment competence among primary education majors at the university level.